Protein “purity,” proteoforms, and the albuminome: critical observations on proteome and systems complexity - Woodland, Breyer; Coorssen, Jens R.; Padula, Matthew P. (Frontiers in Cell and Developmental Biology, 2024)
IntroductionThe identification of effective, selective biomarkers and therapeutics is dependent on truly deep, comprehensive analysis of proteomes at the proteoform level.MethodsBovine serum albumin (BSA) isolated by two different protocols, cold ethanol fractionation and heat shock fractionation, was resolved and identified using Integrative Top-down Proteomics, the tight coupling of two-dimensional gel electrophoresis (2DE) with liquid chromatography and tandem mass spectrometry (LC-MS/MS).Results and discussionNumerous proteoforms were identified in both “purified” samples, across a broad range of isoelectric points and molecular weights. The data highlight several concerns regarding proteome analyses using currently popular analytical approaches and what it means to (i) purify a “protein” if the isolate consists of a wide variety of proteoforms and/or co-purifying species; and (ii) use these preparations as analytical standards or therapeutics. Failure to widely recognize and accept proteome complexity has likely delayed the identification of effective biomarkers and new, more selective drug targets. iTDP is the most logical available analytical technique to effectively provide the necessary critical depth and breadth for complex proteome analyses. Routine analyses at the level of proteoforms will provide the much-needed data for the development and validation of selective biomarkers and drugs, including biologics.